A handbook for teaching and learning in higher education [ enhancing academic practice - Fry, Heather; Ketteridge, Steve; Marshall, Stephanie (Routledge, 2009)
This handbook is sensitive to the competing demands of teaching, research and scholarship and academic management. Dealing with the rapid expansion of the use of technology in higher education and widening student diversity, this updated and expanded edition includes new material on for example, e-learning